Risk of vasectomy failure by ligation and excision with fascial interposition: A prospective descriptive study (2020)
Objective: To evaluate the occlusive failure risk of ligation and excision with fascial interposition vasectomy technique. There are doubts about the effectiveness of this technique largely used in Asia and Latin America. Study design: We conducted a prospective longitudinal observational descriptive study among men who underwent a vasectomy performed under local anesthesia in a clinic specializing in sexual and reproductive health services in Bogotá, Colombia. Three urologists used the Percutaneous No-Scalpel Vasectomy technique to isolate the vas deferens. They then ligated the vas, excised a 1 cm segment between ligations, and ligated the fascia on the prostatic end to cover the testicular end. We requested all patients to submit a semen sample three months after the vasectomy. We defined probable and confirmed vasectomy failure as 1–4.9 million sperm/ml and 5 million sperm/ml or more or any number of motile sperm observed on the last semen sample available, respectively. Results: Among 1149 participants, 581 (51%) had at least one post-vasectomy semen analysis. The overall failure risk was 5.2% (30/581; 95% confidence interval [CI] 3.6%–7.3%) with probable and confirmed failure risk of 1.9% (11/581; 95% CI 1.1%–3.4%) and 3.3% (19/581; 95% CI 2.1%–5.1%), respectively. Older men and one urologist had statistically significant higher risk of overall failure. Conclusion: Our study confirmed that the ligation and excision with fascial interposition vasectomy technique is associated with an unacceptable risk of failure. Implications: Surgeons who use the ligation and excision with fascial interposition vasectomy technique and countries with large vasectomy programs in Asia and Latin America that still recommend this technique should consider adopting alternatives to reduce the failure risk to below 1% as recommended by the American Urological Association. © 2020 Elsevier Inc.